Video Edukasi Terhadap Pengetahuan dan Sikap Calon Pengantin dalam Upaya Pencegahan Stunting - Rahayu, Bintari Dwi; Sutisna, Ma’mun; Raksanagara, Ardini Saptaningsih; Garna, Herry; Sastramihardja, Herry (HB PRESS, 2023)
The prevalence of stunting according to data from the World Health Organization (WHO), is the highest prevalence in the South-East Asia Regional (SEAR), one of which is Indonesia. Efforts to prevent stunting start from pre-conception, by providing knowledge and understanding about fulfilling nutritional intake before pregnancy. This study aims to analyze the effectiveness of using educational videos to prevent stunting on the knowledge and attitudes of prospective brides in efforts to prevent stunting in Banjarbaru City, South Kalimantan.The research method is quantitative with a quasi-experiment in the form of a pretest and posttest design. The sample is 102 people. Consecutive sampling research. Research in January–February 2023. Data analysis used the Mann-Whitney test. The results showed that the pretest intervention group was 76% posttest using educational videos by 88% with a value of p = 0.002 (p <0.05). The attitude of the prospective bride and groom towards preventing stunting pretest was 56% and the posttest using educational videos to prevent stunting was 84% with a value of p = 0.000 (p <0.05). The effectiveness of educational videos with N-Gain is 60.1% which means it is quite effective.Educational videos increase the knowledge and attitudes of prospective brides in preventing stunting and educational videos are effective in increasing the knowledge and attitudes of prospective brides in efforts to prevent stunting in Banjarbaru City, South Kalimantan.